Interpersonal sensitivity mediates the effects of child abuse and affective temperaments on depressive symptoms in the general adult population - Otsuka A (Dove Medical Press, 2017)
Ayano Otsuka,1 Yoshikazu Takaesu,1 Mitsuhiko Sato,1 Jiro Masuya,1 Masahiko Ichiki,1 Ichiro Kusumi,2 Takeshi Inoue1 1Department of Psychiatry, Tokyo Medical University, Tokyo, 2Department of Psychiatry, Hokkaido University Graduate School of Medicine, Sapporo, Japan Background: Recent studies have suggested that multiple factors interact with the onset and prognosis of major depressive disorders. In this study, we investigated how child abuse, affective temperaments, and interpersonal sensitivity are interrelated, and how they affect depressive symptoms in the general adult population. Subjects and methods: A total of 415 volunteers from the general adult population completed the Patient Health Questionnaire-9, the Temperament Evaluation of Memphis, Pisa, Paris, and San Diego-Autoquestionnaire version, the Child Abuse and Trauma Scale, and the Interpersonal Sensitivity Measure, which are all self-administered questionnaires. Data were subjected to structural equation modeling (Mplus), and single and multiple regression analyses. Results: The effect of child abuse on depressive symptoms was mediated by interpersonal sensitivity and 4 affective temperaments, including depressive, cyclothymic, anxious, and irritable temperaments. In addition, the effect of these temperaments on depressive symptoms was mediated by interpersonal sensitivity, indicating the indirect enhancement of depressive symptoms. In contrast to these 4 temperaments, the hyperthymic temperament did not mediate the effect of child abuse on depressive symptoms; its effect was not mediated by interpersonal sensitivity. However, a greater hyperthymic temperament predicted decreased depressive symptoms and interpersonal sensitivity, independent of any mediation effect. Limitations: Because this is a cross-sectional study, long-term prospective studies are necessary to confirm its findings. Therefore, recall bias should be considered when interpreting the results. As the subjects were adults from the general population, the results may not be generalizable towards all patients with major depression. Conclusion: This study suggests that child abuse and affective temperaments affect depressive symptoms partly through interpersonal sensitivity. Interpersonal sensitivity may have a major role in forming the link between abuse, affective temperament, and depression. Keywords: child abuse, affective temperament, TEMPS-A, interpersonal sensitivity, depression, structural equation modeling